2006
DOI: 10.1177/0091270006292628
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ginkgo Biloba Extract on Pharmacokinetics and Pharmacodynamics of Tolbutamide and Midazolam in Healthy Volunteers

Abstract: This study was undertaken to clarify the influence of repeated oral administration of Ginkgo biloba extract (GBE) on CYP2C9 and CYP3A4. CYP2C9 probe (tolbutamide, 125 mg) and CYP3A4 probe (midazolam, 8 mg) were orally administered to 10 male healthy volunteers before and after GBE intake (360 mg/d) for 28 days, and they received 75 g glucose after the dosing of tolbutamide. Plasma drug concentrations and blood glucose levels were measured. The area under concentration versus time curve (AUC0-infinity) for tolb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 35 publications
4
56
1
3
Order By: Relevance
“…After administration for 4 weeks, the bioavailability and maximum plasma concentration of midazolam significantly reduced with no change in the half-life suggestive of intestinal, but not hepatic, induction [113].…”
Section: Other Conditionsmentioning
confidence: 92%
See 1 more Smart Citation
“…After administration for 4 weeks, the bioavailability and maximum plasma concentration of midazolam significantly reduced with no change in the half-life suggestive of intestinal, but not hepatic, induction [113].…”
Section: Other Conditionsmentioning
confidence: 92%
“…This effect was suggested to be as a result of the P-gp inhibitory effect of some ginkgo flavonol constituents, including quercetin, kaempferol, and isorhamnetin, which have been documented [112]. In another study, the effect of the extract of Ginkgo biloba on midazolam (CYP 3A4 substrate) and tolbutamide (CYP 2C9 substrate) was investigated [113]. There, the AUC of tolbutamide following ginkgo intake was significantly reduced.…”
Section: Other Conditionsmentioning
confidence: 99%
“…Many phytochemicals and pharmaceuticals are therapeutic at one dose and toxic at another and synergistic interactions can complicate dosing during long-term medication but experimental data on herbdrug interactions are limited [Fugh-Berman, 2000]. Reports indicate that the interaction of garlic with chlorpropamide [Aslam et al 1979], gingko with tolbutamide [Uchida et al 2006] and St John 0 s wort with gliclazide and tolbutamide [Xu et al 2008;Arold et al 2005] do not change the pharmacokinetics of the pharmaceutical. Administration of antidiabetic herbs with OHDs for the treatment of diabetes could cause a drugherb interaction that might have beneficial or adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs are metabolized by the Phase I and Phase II enzymes; the former is catalyzed by cytochrome P450 (CYP) enzymes, and the latter is catalyzed conjugation enzymes such as glutathione S-transferase (GST) and UDP-glucuronosyltransferase (16). Interactions between some herbal ingredients, such as St John's wort (17) and ginkgo biloba (18), have been documented and shown to be mediated by CYPs, but those for other herbal ingredients remain unknown. We previously showed that feeding mice a diet containing CFE (standardized with 10% forskolin) dose-and time-dependently induced hepatic CYPs and GST enzymes (19).…”
mentioning
confidence: 99%